Phytoremediation of Tofu Liquid Waste Using Water Hyacinth and Water Lettuce to Improve Waste Quality - Salsabila, Al Dira Aisyah; Fitrihidajati, Herlina (LenteraBio : Berkala Ilmiah Biologi, 2024)
Tofu businesses in Indonesia are primarily small-scale businesses that do not have independent wastewater treatment units. Most tofu liquid waste businesses still dispose of tofu liquid waste into nearby bodies of water without processing it first, damaging environmental quality and water pollution. This research aims to describe the influence of various combinations of water hyacinth (Eichhornia crassipes (Mart.) Solms) and water lettuce (Pistia stratiotes Linnaeus) plants in improving the quality of tofu liquid waste in terms of pH and Nitrate parameters. The research was carried out experimentally using a Randomized Block Design (RBD) and one of the treatment factors, namely the combination of plant biomass consisting of 4 treatments (control, 75:25, 50:50, and 25:75). There were 6 six repetitions in the research so there were 24 treatment units. The research was carried out in the Greenhouse Biology Study Program at Surabaya State University, with the parameters measured covered pH and Nitrate on days 0 and 7. pH and Nitrate parameter data were analyzed using one-way ANOVA, then continued with Duncan's test and compared with standards quality according to Minister of Environment Regulation Number 5 of 2014. The results of the research showed that combinations of biomass improved the quality of tofu liquid waste. The most effective combination was 25 water hyacinths : 75 water lettuces that could increase the pH value to 6.9 (6– 9) and reduce Nitrate to 0.21 (30) mg/L.